Adaptive Coatings with Anticorrosion and Antibiofouling Properties. (29th June 2021) - Yimyai, Tiwa; Thiramanas, Raweewan; Phakkeeree, Treethip; Iamsaard, Supitchaya; Crespy, Daniel
Abstract: Biofouling on surfaces immersed in aquatic environment induces catastrophic corrosion of metallic materials in petrochemical infrastructures, maritime facilities, and power plants. To combat the synergistic effect of biofouling and corrosion on the deterioration of metallic materials, smart coatings possessing a dual function of antibiofouling and anticorrosion properties are needed. Herein, redox‐responsive copolymer conjugates are synthesized and employed as coatings with the dual function of biofouling and corrosion mitigation. The dual function of copolymers is attributed to fluorinated units and the corrosion inhibitor 2‐mercaptobenzothiazole (MBT) conjugated via disulfide linkages. Indeed, the disulfide linkages can be cleaved in a reducing environment, yielding controlled release of the corrosion inhibitor MBT during corrosion process. The antibiofouling action against protein adsorption and algal attachment is enabled by cooperation of the repellent characteristic of fluorinated moieties and the biocidal effect of conjugated MBT. Abstract : Adaptive coatings prepared from responsive copolymers display excellent anticorrosion and antibiofouling performance. The copolymers contain fluorinated and redox‐responsive units conjugated with a corrosion inhibitor to allow controlled release of the inhibitor.